2019
DOI: 10.1159/000500347
|View full text |Cite
|
Sign up to set email alerts
|

European Healthy Hydration Awareness Campaign for Dietitians

Abstract: Up to 50% of the adult population fail to meet the recommended total water intake despite the adverse health outcomes associated with chronic low fluid intake. Total fluid intake plays an important role in the energy and nutrient intake of individuals. Dietitians’ role is to advise and guide the population toward a healthier diet. However, based on existing evidence, dietitians’ current knowledge and practices regarding healthy hydration is an area for improvement. The European Healthy Hydration Awareness Camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Poor awareness of dehydration and fluid intake was reported in different countries worldwide ( 10 , 11 ) . Nearly, 50 % of the adult population fail to run across the recommended total water intake despite the adverse health outcomes associated with chronic low fluid intake ( 15 ) . The participants in the present study reported good knowledge of dehydration definition and fluid intake practice.…”
Section: Discussionmentioning
confidence: 99%
“…Poor awareness of dehydration and fluid intake was reported in different countries worldwide ( 10 , 11 ) . Nearly, 50 % of the adult population fail to run across the recommended total water intake despite the adverse health outcomes associated with chronic low fluid intake ( 15 ) . The participants in the present study reported good knowledge of dehydration definition and fluid intake practice.…”
Section: Discussionmentioning
confidence: 99%